MOMORDICA CHARANTIA FRUIT EXTRACT AND GLIBENCLAMIDE SYNERGISTICALLY AMELIORATE CORTICOSTEROID INDUCED DIABETES MELLITUS IN MICE - NEHA SHARMA; SUNANDA PANDA; ANAND KAR (International Journal of Pharma and Bio Sciences, 2014)
As fruit extract of bitter gourd is known to be anti-hyperglycemic and anti-oxidative in nature, in this study we have investigated the possible synergistic effects of Momordica charantia (MC) fruit extract and glibenclamide (GLB) in corticosteroid-induced hyperglycemic mice. Four different groups of animals were treated with dexamethasone alone for first 7 days and then with either MC extract, GLB or MC + GLB along with dexamethasone for next 15 days. On 23rd day, animals were sacrificed; liver and kidney were excised for the estimation of lipid peroxidation (LPO), superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH). Alterations in serum glucose as well as liver histology were also studied. While dexamethasone administration increased the concentration of serum glucose (p<0.001) and LPO (for both renal and hepatic tissues, p<0.001) with a concomitant decrease in SOD, CAT and GSH; administration of MC (150 mg /kg BW) and GLB (500 µg /kg BW) reversed all these indices in - induced diabetic animals. Although, individual treatment with MC or GLB also exhibited positive effects, simultaneous administration of both the test drugs ameliorated hyperglycemia and oxidative stress more effectively. The test extract also exhibited high antioxidative activity in 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical and in 2, 2’-azino-bis (3-ethylbenzothiazoline-6- sulphonic acid (ABTS) radical scavenging assays. Our findings indicate the synergistic benefits of the combined use of Momordica extract and glibenclamide in regulating diabetes mellitus. HPLC analysis suggests the involvement of gallic acid, quercetin and rutin, present in the test extract in the mechanism of observed synergistic action.